DARIYA VIKONSKA’S CREATIVE WORK THROUGH LITERARY-CRITIQUE RECEPTION IN THE 30TH OF THE XX CENTURY (the 120-year anniversary) - Shevchuk, Larysa (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
On the material of epistolary and literary-critique papers in the 30th of the XX century the idea and aesthetic bases, literary strategies and evolutional stages of Dariya Vikonska’s creative work are highlighted and the concept about the specificity of Western Ukrainian literary process of the period mentioned is extended.